Optimalisasi Desa Wisata Air melalui Digitalisasi Promosi dan Implementasi Sustainable Eco-Tourism di Desa Sambigede Kecamatan Sumberpucung - Mohammad Musthofa Al Ansyorie; Muhammad Aris Ichwanto; Gilang Id’fi; Chrisnanda Iqbal Yudhistira; Nur Ira Mega Maharani; Alviando Galih Syahdandi (Universitas Negeri Malang, 2023)
Abstract Sambigede Village is one of the villages located in the administrative area of Sumberpucung District, Malang Regency. As a village with an area belonging to the lowlands, Sambigede village has many locations that have the potential to be developed into a tourist village. Sambigede village itself is a village that is located close to the Karangkates Reservoir. Where the reservoir has the potential to be used as water tourism for tourists who come to it. There are many potential tourist spots that are interesting for tourists to visit. This creates an opportunity for Sambigede Village to develop into a rural tourist destination. Some of these potentials need to be maximized so that Sambigede Village becomes more attractive to tourists. So that there is a need for a touch and application of science and technology for the purposes of developing Sambigede Village with the Digitalization of Promotion and Implementation of Sustainable Eco-Tourism. Development for Implementation in this case can be poured in the form of a description of the Application and Website design for Sambigede Village. The output targeted at community service is in the form of a website and application for promoting the water tourism village of Sambigede Village. as well as articles from this activity published in the Journal of Community Service Sinta 5. This service seeks to obtain Intellectual Property Rights in the form of Copyrights and strive for Patents and obtain the product of the application of science and technology as one part of the creation of cooperation or partnerships between the community and universities. Abstrak Desa Sambigede merupakan salah satu desa yang berada dalam kawasan administratif Kecamatan Sumberpucung Kabupaten Malang. Sebagai desa dengan wilayah yang tergolong pada dataran rendah, desa Sambigede memiliki banyak lokasi yang sangat berpotensi untuk dikembangkan menjadi desa wisata. Desa Sambigede sendiri merupakan desa yang letaknya dekat dengan Waduk Karangkates. Dimana waduk tersebut berpotensi untuk dijadikan wisata air bagi para turis yang mendatanginya. Banyaknya potensi spot wisata yang menarik untuk didatangi para turis. Hal tersebut menjadikan peluang bagi Desa Sambigede untuk berkembang menjadi destinasi wisata pedesaan. Beberapa Potensi tersebut perlu dimaksimalkan agar Desa Sambigede ini menjadi lebih menarik bagi wisatawan. Sehingga perlu adanya sentuhan dan aplikasi IPTEKS untuk keperluan pengembangan Desa Sambigede dengan Digitalisasi Promosi dan Implementasi Sustainbale Eco-Tourism. Pengembangan untuk Implementasi dalam hal ini dapat dituangkan berupa gambaran desain Aplikasi dan Website untuk Desa Sambigede. Luaran yang ditargetkan pada pengabdian kepada masyarakat ini berupa website dan aplikasi promosi desa wisata air Desa Sambigede. serta Artikel hasil kegiatan ini dipublikasikan di Jurnal Pengabdian Kepada Masyarakat Sinta 5. Pengabdian ini berusaha untuk memperoleh Hak Kekayaan Intelektual berupa Hak Cipta dan diupayakan Paten dan didapatkan produk penerapan IPTEKS sebagai salah satu bagian dari terciptanya kerjasama atau kemitraan antara masyarakat dan perguruan tinggi.